Moral Economies and Practicing Moral Laws in Religions - Maria Frahm-Arp (Journal for the Study of Religion)
The second edition of the Journal for the Study of Religion for 2022 explores religion and moral economies as well as religion and moral legal practices. With this particular focus, the timing of this edition is poignantly relevant as we face a global recession, the war in the Ukraine, ongoing and deep-rooted corruption in various political systems throughout the world, and the rise of a form of Christianity – prophetic Pentecostalism – which appears to have a weak understanding of morality and ethics.